2021
DOI: 10.1111/ina.12845
|View full text |Cite
|
Sign up to set email alerts
|

Volatile organic compound and particulate matter emissions from an ultrasonic essential oil diffuser

Abstract: Ultrasonic essential oil diffusers (EODs) are a popular type of indoor scenting source. We performed a chamber study in which we measured the emissions from EODs used with lemon, lavender, eucalyptus, and grapeseed oils. Over the course of 15 min, the most abundant VOCs released from lemon, lavender, eucalyptus, and grapeseed oils were 2.6 ± 0.7 mg of d‐limonene, 3.5 ± 0.4 mg of eucalyptol, 1.0 ± 0.1 mg of linalyl acetate, and 0.2 ± 0.02 mg of linalyl acetate, respectively. Each oil had a unique particulate ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 76 publications
(235 reference statements)
0
7
0
Order By: Relevance
“…Indoor sources of PM often involve combustion, such as cooking, smoking, and burning incense or candles [2][3][4][5]. However, PM is also generated by non-combustion sources such as electronic air fresheners and essential oil diffusers [6]. PM can also be generated or resuspended by movement, cleaning, and other agitation of surfaces [2].…”
Section: List Of Tablesmentioning
confidence: 99%
“…Indoor sources of PM often involve combustion, such as cooking, smoking, and burning incense or candles [2][3][4][5]. However, PM is also generated by non-combustion sources such as electronic air fresheners and essential oil diffusers [6]. PM can also be generated or resuspended by movement, cleaning, and other agitation of surfaces [2].…”
Section: List Of Tablesmentioning
confidence: 99%
“…The detection of d‐limonene and β‐pinene (approximately 21 and 3 ppb, respectively) in the room where no essential oil was used could either be due to mixing of air between the two adjacent testing rooms or ambient d‐limonene and β‐pinene from the use of consumer cleaning products in other areas of the building 44 . Although the VOC concentrations during grapeseed tests are unavailable, they are presumably very low as the relevant chemicals were not detected in a sample of pure grapeseed oil and our former chamber tests found the amount of eight measured VOCs emitted by a diffuser using grapeseed oil to be all negligible 45 …”
Section: Resultsmentioning
confidence: 77%
“…Compared with self‐reported perception or simulated work performance, the cognitive tests used in this study are more robust and less likely to be affected by recall bias, personal experience, and working skills; also, as each task targets specific brain functions, when combined they are potentially more sensitive in capturing mild changes in cognitive performance. The quantity of essential oil was strictly 200 μl in every trial and DI water was used (our previous study found that PM emission rate increased approximately tenfold and fluctuated appreciably when tap water was used compared with DI water 45 ), ensuring the exposures were reasonably consistent. In addition, the between‐subject design in the current study enabled concurrent contrasts and thus addressed many potential confounders such as time‐of‐day and day‐of‐week effects, although the effect size can be smaller (less likely to find statistically significant results) because of individual variations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While our detailed examination of chemically-dependent processes focused on THS, these results are also relevant to other combustion emissions related to indoor air quality (e.g., biomass burning or cooking), outdoor air quality (as seen in past wildre plume dilution studies 102,103 ), and aqueous-phase emissions/uptake, such as with vaping, 104,105 waterpipe tobacco smoking, 106 or humidiers. 107 5.2.1 Effect of environmental variables on THS reservoirs. First, further research is necessary to examine the effects of environmental conditions on off-gassing rates and composition for various reservoirs over extended timescales, including beyond those studied here.…”
Section: Opportunities For Future Workmentioning
confidence: 99%